Refleksi Hermeneutika Dalam Studi Islam - Eko Nopriyansa; Rama Wijaya Kesuma Wardani (STAI Bumi Silampari, 2020)
The purpose of this literature analysis is to find out the reflection of hermeneutics in Islamic scientific studies, in this effort the method used is qualitative descriptive, namely the study of the literature literature by comprehensively explaining the fundamental problems that become the object of study in research, so that in this study the results of the analysis are found. shows that hermeneutics in Islamic studies can be considered, although it requires analysis and improvement of several aspects of methodology and related problems that are indicated to create a crucial scientific nuance.